The Scharff technique: training military intelligence officers to elicit information from small cells of sources - Granhag, Pär Anders (Psychology, crime & law, 2020)
Studies have demonstrated the efficacy of the Scharff technique for gathering human intelligence, but little is known about how this efficacy might vary among different samples of practitioners. In this training study we examined a sample of military officers (n = 37). Half was trained in the Scharff technique and compared against officers receiving no Scharff training. All officers received the same case file describing two sources holding information about a terrorist attack. University students (n = 74) took the role of the semi-cooperative sources. Scharff-trained officers adhered to the training as they (1) aimed to establish the ‘knowing-it-all’ illusion, (2) posed claims as a means of eliciting information, and (3) asked fewer explicit questions. The ‘untrained’ officers asked many explicit questions, questioned the reliability of the provided information, pressured the source, and displayed disappointment with the source's contribution. Scharff-trained officers were perceived as less eager to gather information and left their sources with the impression of having provided comparatively less new information, but collected a similar amount of new information as their untrained colleagues. The present paper both replicates and advances previous work in the field, and marks the Scharff technique as a promising technique for gathering human intelligence.